LEGAL PROTECTION TOWARDS EXPORTERS AND IMPORTERS IN INTERNATIONAL TRADE TRANSACTIONS USING LETTER OF CREDIT (L/C) AS A PAYMENT SYSTEM AT PT. BANK MAYBANK INDONESIA TBK BRANCH OF BENGKULU - Dinda Estasari; Widya N. Rosari; Tito Sofyan (Universitas Bengkulu, 2021)
This study aims to examine and to analyze the legal protection of exporters and importers in international trade transactions using Letter of Credit (L/C) as a payment system at PT. Bank Maybank Indonesia Tbk branch of Bengkulu. The type of this study was normative legal research with descriptive analytical research design. The result of this study indicated that in an international payment system that used L/C, both exporters and importers were protected, thus exporters did not have to worry about their goods not being paid for, while importers did not need to worry that the goods they bought did not arrive or that they would lose payment, because the bank would guarantee this matters if the required documents were appropriate. PT. Bank Maybank Indonesia Tbk branch of Bengkulu, in protecting its customers, must have considerations both based on the provisions of national banking regulations and based on the applicable banking practices. The efforts made by banks to protect exporters and importers were such as banks have to implement good corporate governance, apply Know Your Customer principles including the principle of prudence in providing L/C facilities, apply the Know Your Employee principle. Moreover, it was necessary to apply optimal sanctions in case of violation of procedures. The L/C arrangements at PT. Bank Maybank Indonesia Tbk branch of Bengkulu adheres to UCP 600 so that it can avoid differences or misinterpretation between the transacting parties as far as possible.